Характеристика впливу 4-[4-оксо -4H-хіназолін -3-іл ] бензойної кислоти (ПК-66) на перебіг адреналінової міокардіодистрофії в щурів за даними біохімічних досліджень - Джигалюк, О. В.; Степанюк, Г. І.; Заічко, Н. В.; Коваленко, Сергій Іванович; Шабельник, Костянтин Петрович; Dzhyhaliuk, O. V.; Stepaniuk, H. I.; Zaichko, N. V.; Kovalenko, S. I.; Shabelnyk, K. P. (My University, 2018)
Згідно з даними літератури, провідною причиною смертності населення України є серцево-судинні захворювання, поширеність яких за останні 25 років зросла втричі й на сьогодні становить 801,6 на 100 тис. населення. Це зумовлює необхідність пошуку нових хімічних сполук, придатних для створення кардіопротекторів із кращим профілем безпечності та вищим ступенем ефективності. Метою дослідження було охарактеризувати вплив 4-[4-оксо-4Н-хіназолін-3-іл] бензойної кислоти (сполуки ПК-66) порівняно з кордароном на процеси вільнорадикального окиснення, ендотеліальне продукування нітроген монооксиду та активність маркерних ензимів цитолізу кардіоміоцитів при адреналіновій міокардіодистрофії (АМД) у щурів. Дослідження проведено на 28 нелінійних щурах обох статей масою 165–220 г, поділених на чотири групи: 1-ша (n=7) – інтактні щури; 2-га (n=7) – щури з АМД без лікування (контроль); 3-тя (n=7) – щури з АМД, ліковані сполукою ПК-66 (10 мг/кг, внутрішньочеревно); 4-та (n=7) – щури з АМД, ліковані кордароном (10 мг/кг, внутрішньочеревно). According to the literature the leading cause of mortality among the population of Ukraine are cardiovascular diseases, what incidence tripled over the past 25 years and today stands at 801.6 in 100 000. It necessitates a search for new chemical compounds, suitable for creating manufacturing with a better safety profile and a high degree of efficiency. The aim of the study was to describe the effect of 4-[4-oxo-4N-quinazoline-3- il] benzoic acid (PC-66), compared with kordaron on the processes of free radical oxidation, endothelial nitric oxide production and activity of marker enzymes cytolysis cardiomyocytes adrenaline myocardiodystrophy (AMD) in rats. The study was conducted on 28 nonlinear rats of both sexes (weight – 165–220 grams), divided into four groups: group I (n=7) – intact rats; group II (n=7) – rats with untreated AMD (control); group III (n=7) – rats with AMD treated with entity PC-66 (10 mg/kg intraperitoneally (i/p)); Group IV (n=7) – rats with AMD treated with kordaron (10 mg/kg, i/p). Research shown that the development of a pilot AMD in rats was characterized by increased free radical oxidation processes, depletion of antioxidant defense system (with decreased content of GSH, activity of superoxide dismutase and glutathione peroxidase), oppression of endothelial NO production. The most expressive metabolic disturbances were registered in the acute period of AMD (as of 2nd day). The use of 4-[4-oxo-4N-quinazoline-3-il] benzoic acid (PC-66, 10 mg/kg, i/p) provided an expressive cardioprotective effect which was compared with kordaron (10 mg/kg, i/p) at various stages of AMD.
Characteristics of influence of 4-[4-oxo -3 h-quinazoline -3-yl] benzoic acid (PC-66) on a corse of adrenaline myocardiodystrophy in rats according to biochemical research
Keywords: адреналінова міокардіодистрофія; кордарон; 4-[4-оксо-4Н-хіназолін-3-іл] бензойна кислота; кардіопротекторна дія; adrenaline myocardial dystrophy; cordarone; 4-[4-oxo-4H-quinazoline-3-il] benzoic acid; cardioprotective activity